Les accompagnateurs dans l’enseignement supérieur. Quel apprentissage suite aux affordances saisies dans un environnement multiculturel ? - Patricia Rached (Éducation et Socialisation)
Based on socio-constructivism, this qualitative study uses semi-directive interviews with 18 faculty members who act as advisors in six Faculties at the Saint-Joseph University of Beirut. Results showed that some factors help faculty members in developing their own learning while providing support to students ; these factors are interrelated : students’ needs correlated with the socio-economic background, advisors’ attitude that makes the most out of academic and interpersonal affordance, and advisors’ learning styles that seem to be influenced by their professional environment. Consequently, advisors enhance their skills at different levels : cognitive, methodological, emotional and human. They make use of 4 modes of learning : praxis, social interaction, trial and error, and self-documentation.